2022
DOI: 10.3390/biology11030473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic High-Frequency rTMS Protocol on Respiratory Neuroplasticity Following C2 Spinal Cord Hemisection in Rats

Abstract: High spinal cord injuries (SCIs) lead to permanent diaphragmatic paralysis. The search for therapeutics to induce functional motor recovery is essential. One promising noninvasive therapeutic tool that could harness plasticity in a spared descending respiratory circuit is repetitive transcranial magnetic stimulation (rTMS). Here, we tested the effect of chronic high-frequency (10 Hz) rTMS above the cortical areas in C2 hemisected rats when applied for 7 days, 1 month, or 2 months. An increase in intact hemidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Additionally, TMS may induce respiratory plasticity by reducing inflammatory responses. A recent study found that 10-Hz rTMS treatment could reduce inflammation of the spinal cord (C1-C3) in rats with C2 hemisection (reduced CD68 and Iba1 labeling) and accelerate the intracellular plasticity of PMNs, thereby enhancing the respiratory descending fibers in the ventrolateral funiculus (increased GAP-43-positive fibers), indicating that chronic high-frequency rTMS can improve respiratory dysfunction after cervical spinal cord injury and induce neuronal plasticity by reducing harmful post-traumatic inflammatory processes ( Michel-Flutot et al, 2022 ).…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…Additionally, TMS may induce respiratory plasticity by reducing inflammatory responses. A recent study found that 10-Hz rTMS treatment could reduce inflammation of the spinal cord (C1-C3) in rats with C2 hemisection (reduced CD68 and Iba1 labeling) and accelerate the intracellular plasticity of PMNs, thereby enhancing the respiratory descending fibers in the ventrolateral funiculus (increased GAP-43-positive fibers), indicating that chronic high-frequency rTMS can improve respiratory dysfunction after cervical spinal cord injury and induce neuronal plasticity by reducing harmful post-traumatic inflammatory processes ( Michel-Flutot et al, 2022 ).…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…The use of preclinical models is consequently required to decipher the inflammatory and plasticity processes involved. The rodent cervical C2 lateral hemi-section (C2HS) model is the most widely used to evaluate the impact of high SCI on spinal neuroplasticity and neuroinflammation related to the phrenic system [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contralateral side of the C2 hemi-injury remains intact, allowing the survival and recovery of the animal. This also leads to inflammatory processes at the site of injury [ 19 , 20 ], but also in the aera of deafferented motoneurons [ 9 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to further explore the potential of SPG302 in other models of spinal cord injury (e.g. contusion models), extending to large animal models, and as part of a combined approach with therapies such as intermittent hypoxia with and without task‐specific training (Vose et al., 2022), and spinal and cortical stimulation strategies (Michel‐Flutot et al., 2022), which aim to harness intrinsic neuroplasticity, recovering neural drive to ensure adequate electrical activation of the respiratory muscles for the crucial act of breathing.…”
mentioning
confidence: 99%
“…It would be interesting to further explore the potential of SPG302 in other models of spinal cord injury (e.g. contusion models), extending to large animal models, and as part of a combined approach with therapies such as intermittent hypoxia with and without task-specific training (Vose et al, 2022), and spinal and cortical stimulation strategies (Michel-Flutot et al, 2022), which aim to harness intrinsic neuroplasticity, recovering neural drive to ensure adequate electrical activation of the respiratory muscles for the crucial act of breathing. The innovative study by Fogarty et al (2023) highlights the potential application of pegylated benzothiazole derivatives for the recovery of respiratory muscle activity following spinal cord injury, providing renewed focus on the potential of pharmacotherapy for neural regeneration and rehabilitation in spinal cord injury.…”
mentioning
confidence: 99%